Equipment network management security of electrical power PTN - Yun LIU; Guojun LIU; Jianwei REN; Jian LI (Dianxin kexue)
In order to solve the problem that the power PTN equipment management system vulnerable to be attacked and vulnerability,the risk factors of electric power PTN equipment network management system were proposed based on the architecture of PTN equipment network management system.From the factors of economic,security and maintenance efficiency,the network deployment of equipment network management system based on MPLS-VPN power data communication network was proposed.The out-band and in-band DCN security deployment plan of province-level,city-level and country-level was put forward.Finally,the boundary security program was proposed for the interaction between the PTN equipment network management system and other systems.